EVALUASI PROGRAM PERSIAPAN TES TOEFL YANG DISELENGGARAKAN OLEH LPIA DI AKADEMI MARITIM YOGYAKARTA - Risgar Friassantano; Nanda Kristia Santoso; Marina Lidya (Sekolah Tinggi Pariwisata Mataram, 2023)
Abstrak The objectives of the research are (1) to describe the evaluation of TOEFL-Preparation program designed by Lembaga Pendidikan Indonesia-Amerika based on CIPP, and (2) to find out the influence of the program toward the students based on CIPP. The research was an Evaluation Research. The researcher employed CIPP (Context, Input, Process, and Product) evaluation model by Stufflebeam (2003). The data were collected through observation, in-depth-interview, and documentation. The data were analysed by using Miles and Huberman and Saldana’s (2014) model of qualitative data analysis. The result of the study shows that the TOEFL-preparation program held at Akademi Maritim Yogyakarta has been design well enough. It is reflected from 3 components of CIPP by Stufflebeam (2003). The context of program is the program has been designed to fulfil the needs of a campus. The program aims to help the students to achieve TOEFL scores standardized by their campus by giving some strategies for TOEFL Test. Almost all input components of program have good characteristics. However, there are some components that must be improved, such as: students, facilities and infrastructures. The program also has significance influences toward the students. It is reflected in the last component of CIPP. That is product of the program. The result also revealed that most students taking TOEFL-preparation program have improvement in their TOEFL score. They have achieved scores demanded by their campus. Besides, the program also brings positive impact to the students. Some of them regard that the program encouraged and motivated them to learn English more